Infants' physiological responses to emotionally salient media with links to parent and child, empathy, prosocial behaviors and media use. (February 2023) - Stockdale, Laura A.; Porter, Chris L.; Reschke, Peter J.; Booth, McCall; Coyne, Sarah M.; Stephens, Jane; Memmott-Elison, Madison K.
Abstract: Infants engage in prosocial behaviors from very young ages and their prosocial behavior is clearly present by the second year of life. Physiological regulation has been related to infants' emerging prosocial behavior, with infants with better regulatory skills displaying increased prosocial behavior. Media use and media content has also been related to infants emerging prosocial behavior. The current study examined individual differences in infants' vagal regulation (as physiological marker of regulatory skills, N  = 269) while engaging with emotionally salient media and how individual differences in vagal regulation were related to parental and child empathy, prosocial behavior, and media use. The study included parent-infant dyads co-viewing a brief educational but emotionally salient video clip, an observational prosocial sticker and sharing tasks, and parental reports of infants' prosocial media use, empathy, and parents' own prosocial media use, prosocial behavior, and empathy. Most infants displayed an increase in RSA while co-viewing the media clip relative to a neutral baseline. Infants with higher RSA (a sign of better regulation) during co-viewing displayed more prosocial behavior in the sticker and pen drop tasks, were rated as more empathic, and had primary caregivers who engaged with more prosocial media than infants who showed a decrease in RSA (e.g., more immature regulatory skills) during co-viewing. Results suggest the importance of vagal regulation in the presence of others' emotions for infants emerging prosocial behavior. Results also suggest that parents' own prosocial media viewing may indirectly influence on the way infants' respond physiologically to others' emotions. Highlights: Infants watched an educational film clip while their heart rate was recorded. Most infants displayed an increase in regulatory skills while co-viewing the media clip. Infants with more mature regulatory skills displayed more prosocial behavior. Infants with more mature regulatory skills had parents who watched more prosocial media. Parents' own prosocial media viewing may indirectly influence infants' response to emotions.